Ensuring Competitiveness of Logistics Service by Selecting the Type of Storing Single-Piece Cargoes - Trunina, Iryna; Zahorianskyi, Volodymyr; Zahorianska, Olena; Moloshtan, Dmytro (International Journal of Engineering and Technology, 2018)
Efficient transportation of cargoes from the point of the cargo traffic start to the final consumers can significantly influence competitiveness of logistics service that leads to the necessity of analysing the known approaches to substantiating the selection of the storing type (pile storage or rack storage) when warehousing single-piece cargoes. To formalize the problem of selection based on the analysis, the authors develop the model, which is suggested to use the quantity of the stored pallets with single item cargoes. The calculations according to the suggested mathematical model envisage intensive computations with repeated calculations; therefore the corresponding recursive algorithms are developed for this mathematical model. The corresponding recursive algorithms for the model are easily realized in the software product. The developed algorithms can be easily realized in the software product with graphic interface on the enterprises delivering logistics services to enhance their competitiveness.Â Â